Linking locomotor performance to morphological shifts in urban lizards (2018)
Urban habitats are drastically modified from their natural state, creating unique challenges and selection pressures for organisms that reside in them. We compared locomotor performance of Anolis lizards from urban and forest habitats on tracks differing in angle and substrate, and found that using artificial substrates came at a cost: lizards ran substantially slower and frequently lost traction on man-made surfaces compared to bark. We found that various morphological traits were positively correlated with sprint speed and that these same traits were significantly larger in urban compared to forest lizards. We found that urban lizards ran faster on both man-made and natural surfaces, suggesting similar mechanisms improve locomotor performance on both classes of substrate. Thus, lizards in urban areas may be under selection to run faster on all flat surfaces, while forest lizards face competing demands of running, jumping and clinging to narrow perches. Novel locomotor challenges posed by urban habitats likely have fitness consequences for lizards that cannot effectively use manmade surfaces, providing a mechanistic basis for observed phenotypic shifts in urban populations of this species. © 2018 The Author(s) Published by the Royal Society. All rights reserved.